2004
DOI: 10.1177/0899764003257494
|View full text |Cite
|
Sign up to set email alerts
|

Typology of Religious Characteristics of Social Service and Educational Organizations and Programs

Abstract: The general term faith-based organizations is inadequate because no clear definition exists of what it means to be faith-based. This article proposes an inductively derivedsixfold typology of social service and educational organizations and programs based on their religious characteristics: faith-permeated, faith-centered, faith-affiliated, faithbackground, faith-secular partnership, and secular. The typology is divided into two sections, organizations and programs, recognizing that the religious characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
171
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(177 citation statements)
references
References 8 publications
5
171
1
Order By: Relevance
“…), two questions about the general orientation of the congregation to community outreach activities designed to help classify the congregation using the Sider and Unruh (2004) We conducted a small pilot test with 20 FBOs selected from the area of the CIL located in the smallest metropolitan area to compare phone versus mail-based survey procedures. We found that making a connection with respondents by phone was very difficult and time consuming, and produced few responses compared to the mailed survey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…), two questions about the general orientation of the congregation to community outreach activities designed to help classify the congregation using the Sider and Unruh (2004) We conducted a small pilot test with 20 FBOs selected from the area of the CIL located in the smallest metropolitan area to compare phone versus mail-based survey procedures. We found that making a connection with respondents by phone was very difficult and time consuming, and produced few responses compared to the mailed survey.…”
Section: Methodsmentioning
confidence: 99%
“…Pragmatically, researchers also point out that several of the largest social service providers in the United States are FBOs and that they are among the largest recipients of federal funding. Sider and Unruh (2004) note a lack of agreement on what constitutes an FBO. They describe the characteristics of six types of human service organizations, ranging from faith-permeated to secular programs.…”
Section: Introductionmentioning
confidence: 99%
“…These NGOs justify their actions as being inspired and guided by the teachings and principles of Christianity or from a particular interpretation or school of thought within Christianity ( [27], p. 1). In essence, Christian faith-related NGOs are those [28,29] in which:…”
Section: Christian Faith-related Ngos Managing Identitiesmentioning
confidence: 99%
“…What counts as meeting these different standards can be a moving target, varying according to which funding source or to which specific network players the organization must relate at any given time. Using the terminology developed by Sider and Unruh [16], the two organizations that were not sustained were categorized by the CFBI evaluation as "faith-background" as opposed to the "faith-centered" approaches in the three more successful cases. All three of the sustained organizations insisted on staying true to their faith commitments as the essential grounding for their work and as essential to participant outcomes, even while abiding by the spirit of church-state restrictions that accompanied their state grant.…”
Section: Faith-inspired Commitments and Persistencementioning
confidence: 99%
“…On the other hand, their characteristic ways of working with program participants-marked by adaptive relationship-building that meets clients where they are rather than deployment of static, pre-set programs-fit uneasily into a social service world increasingly marked by bureaucratic norms, standardized programs, and rigid accountability metrics. While much attention has focused on how government can partner with these organizations within church-state legal restrictions [15,16], the larger question posed is how to integrate these types of organizations into reciprocal network relationships governed by prevailing professional norms and standards. Many of the same issues are raised by partnerships with secular nonprofits of limited size and capacity, although they are not the focus of this analysis.…”
Section: Introductionmentioning
confidence: 99%